Statistics of Water Vapor Variability in the Tropics from Airborne Lidar - Sadykov, Aidar (2019)
The tropics are a forge of Earth’s climate, since they store a considerable part of terrestrial water vapor, which is a key greenhouse effect contributor. Water vapor is extremely variable in space and time due to inhomogeneous distribution of humidity sources and sinks intertwined with complex atmospheric dynamics. This presents challenges to water vapor parametrization in numerical climate and weather models given the ongoing climate change, effectively increasing the uncertainty of predictions. In order to bridge the gap and elucidate water vapor variability, we analyze WALES (a differential absorption lidar) and dropsonde data on relative humidity and water vapor mass mixing ratio from NARVAL, an airborne campaign near the Lesser Antilles in December 2013 and August 2016. Firstly, we identify four physically different atmospheric condition classes of regions in lidar curtains: winter undisturbed, summer undisturbed, summer Saharan dust and summer tropical storm; and inspect them with the help of three statistical methods: statistical moments, probability density functions and Fourier analysis. As the result, characteristic behavior of water vapor in the planetary boundary layer, the cloud layer and the free atmosphere is described in terms of mean, standard deviation and skewness profiles of relative humidity; probability density functions of water vapor mass mixing ratio across ranging horizontal slices of the cloud layer; and Fourier power spectra of mean class relative humidity profiles. Vertical lidar profiles feature high variability in the cloud layer at altitudes between 500 m and 2500 m (above mean sea level), where humid clouds are interleaved with drier gaps between them. The free atmosphere between 2500 m and 9000 m typically contains only minor humidity oscillations around a very dry central value due to intermittently occurring wetness bubbles. Storms, however, are capable of bringing wet air parcels above the capping inversion and disturbing the entire altitude range of the free atmosphere. ...